2020
DOI: 10.4103/psychiatry.indianjpsychiatry_587_19
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about obstructive sleep apnea among medical undergraduate students: A long way to go!

Abstract: Objective: The aim is to study the knowledge and attitude of medical undergraduate students regarding obstructive sleep apnea (OSA). Materials and Methods: This cross-sectional study involved 324 medical undergraduate students in clinical semesters. Knowledge and attitude regarding adult OSA were assessed using the obstructive sleep apnea knowledge and attitude (OSAKA), and to evaluate the same about childhood OSA, OSAKA-KIDS was used. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
(20 reference statements)
1
5
1
Order By: Relevance
“…Thus, the fact that in our study, only 11.6% of the dentists involved in the search believed they had high knowledge and that only half of the interviewees (50.4%) thought they could handle young patients with OSA is not surprising, although this highlights the need for improving pediatric OSA education. Lower percentages of self-confidence in managing OSA in children were found among physicians (29.2%) in a study by Uong et al ( 19 ) and among medical students in a study by Wadhwa et al ( 33 ).…”
Section: Discussionmentioning
confidence: 86%
“…Thus, the fact that in our study, only 11.6% of the dentists involved in the search believed they had high knowledge and that only half of the interviewees (50.4%) thought they could handle young patients with OSA is not surprising, although this highlights the need for improving pediatric OSA education. Lower percentages of self-confidence in managing OSA in children were found among physicians (29.2%) in a study by Uong et al ( 19 ) and among medical students in a study by Wadhwa et al ( 33 ).…”
Section: Discussionmentioning
confidence: 86%
“…Different studies that assessed knowledge regarding OSA conducted on nursing practitioners and medical undergraduate students reported fair knowledge among the former, owing to years of experience, (Valerio & Heaton, 2014) but among the latter, the knowledge related to OSA was limited. (Goyal et al, 2018;Ozoh OB et al, 2015;Wadhwa R et al, 2020;Zaidi et al, 2021)In India, medical students and graduates were largely unawareof the incidence of OSA in adults and children. (Goyal et al, 2018;Wadhwa R et al, 2020) (Goyal et al, 2018;Wadhwa R et al, 2020) This was consistent with the current study findings where the majority of the nursing students had inadequate knowledge about OSA.…”
Section: Discussionmentioning
confidence: 99%
“…(Goyal et al, 2018;Ozoh OB et al, 2015;Wadhwa R et al, 2020;Zaidi et al, 2021)In India, medical students and graduates were largely unawareof the incidence of OSA in adults and children. (Goyal et al, 2018;Wadhwa R et al, 2020) (Goyal et al, 2018;Wadhwa R et al, 2020) This was consistent with the current study findings where the majority of the nursing students had inadequate knowledge about OSA. On item-wise analysis, it was found that they lacked adequate knowledge related to the treatment of OSA, followed by symptoms, diagnosis, then epidemiology, and pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations